The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.2139/ssrn.2589840
|View full text |Cite
|
Sign up to set email alerts
|

Recessions are Not Good for Your Health: The Counter-Cyclical Health Outcomes Revisited

Abstract: The net, positive, effect of unemployment at conception on birth outcomes in developed countries is likely overestimated in the literature. This is the consequence of ignoring the effects of unemployment during pregnancy. Using data from Israel, we not only confirm this finding but also find that the harmful effects of unemployment in the third trimester are large enough to offset any preceding positive effects. Stress and nutritional deficiencies due to economic contractions during pregnancy are at least as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…It shows that the past economic fluctuation has significant effect on the child's chances of survival. These findings are similar that of Maruthappu, Watson, Watkins, Zeltner, Raine and Atu [9]; Paxson and Schady [12]; Chung and Muntaner [10], who have investigated the relationship between economic fluctuations and child mortality rates. The findings of this study are contrary to the procyclical relationship found by Miller and Urdinola [14]; Dehejia and Lliras-Muney [15] and Abdala, F., R. Geldstein and S. Mychaszula [21].…”
Section: Conclusion and Policy Recommendationssupporting
confidence: 87%
See 1 more Smart Citation
“…It shows that the past economic fluctuation has significant effect on the child's chances of survival. These findings are similar that of Maruthappu, Watson, Watkins, Zeltner, Raine and Atu [9]; Paxson and Schady [12]; Chung and Muntaner [10], who have investigated the relationship between economic fluctuations and child mortality rates. The findings of this study are contrary to the procyclical relationship found by Miller and Urdinola [14]; Dehejia and Lliras-Muney [15] and Abdala, F., R. Geldstein and S. Mychaszula [21].…”
Section: Conclusion and Policy Recommendationssupporting
confidence: 87%
“…Conley and Springer [10] equally found that state spending, which varied according to the institutional structure of the welfare state, negatively affected infant mortality. Studies like Paxson and Schady [11], and Asali [12] equally found negative relationship between macroeconomic variables and infant mortality rates.…”
Section: Literature Reviewmentioning
confidence: 94%